2015
DOI: 10.14260/jemds/2015/1607
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Dexamethasone as an Adjuvant to Bupivacaine in Supraclavicular Brachial Plexus Block

Abstract: AIMS:Brachial plexus nerve blocks have analgesic and opioid sparing benefits for upper extremity surgery. Single-injection techniques are limited by duration of local anaesthetic agents, however Continuous block techniques can be used for prolonged anaesthesia and analgesia but it presents management challenges. The study was designed to compare the effects of dexamethasone administered as an adjunct to bupivacaine in supraclavicular brachial plexus block on the onset,duration and postoperative analgesia follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…We included 93 trials (n = 5668) in the network meta‐analysis for motor block duration [32–43, 45, 48, 50–63, 65, 67, 68, 70–111, 113–131]. The mean (95%CI) duration of motor block in the control group was 369 (330‐408) min.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We included 93 trials (n = 5668) in the network meta‐analysis for motor block duration [32–43, 45, 48, 50–63, 65, 67, 68, 70–111, 113–131]. The mean (95%CI) duration of motor block in the control group was 369 (330‐408) min.…”
Section: Resultsmentioning
confidence: 99%
“…The full‐text manuscripts of the remaining 312 studies were assessed. After including studies from hand searches and revision of search, we identified a total of 100 studies for inclusion in this network meta‐analysis [32–131]. The study flow chart is in online Supporting Information Figure S1.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies reported the prolonged duration of sensory and motor block when dexamethasone was used as an adjuvant with bupivacaine and lignocaine in brachial plexus block, but they differed regarding the onset of sensory and motor block. [ 7 8 9 10 11 ] Effect of dexamethasone with bupivacaine was studied in interscalene block and it was concluded that the sensory and motor block was prolonged and use of opioid was reduced postoperatively using dexamethasone. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] Many other studies reported the prolonged duration of sensory and motor block when dexamethasone was used as an adjuvant with bupivacaine and lignocaine in brachial plexus block, but they differed regarding the onset of sensory and motor block. [ 10 11 12 13 ] Effect of dexamethasone with bupivacaine was studied in interscalene block, and it was concluded that the sensory block was prolonged and use of opioid was reduced post-operatively using dexamethasone. [ 14 ] In our study we observed that adding dexamethasone (8 mg) to levobupivacaine not only delayed the time for the first rescue analgesic but also decreased the number of rescue analgesics required.…”
Section: Discussionmentioning
confidence: 99%